STUDY OF CONSUMER ACCEPTANCE ON GRILLED CAKE FORMULATION OF FISH CAKE COATED Cyprinus carpio - Ferdi Gusmanto; Mirna Ilza; Desmelati ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research war aimed to evalute the formulation of fish grilled cakeprocessing which was made from Cyprinus carpio. The parameter analysis wasorganoleptic, chemical analysis (protein content), and microbiology analysis i.e.total plate count. The method used for this research was completely randomizeddesign (CRD) with 4 levels treatment, i.e. O0 (control), O1 (25% of meat fish), O2(35% of meat fish), and O3 (50% of meat fish). The resultshowed that grilled cakeof Cyprinus carpio with O3 50% of meat fish was the best treatment. Theorganoleptic value for apperance was 3.00, taste 3.80, texture 3.16, and aroma3.50. Prohemical analysis value for protein content was 16.64, and total platecount 10.3 cel/gram.Keyword: Consumer acceptance, Cyprinus carpio,fish cake coated